Implications of annual budgeting on the execution of Brazilian Navy investments - Cruz, Vinicius Wood da (2024)
Brazil has a vast maritime area called the “Blue Amazon,” which is rich in natural resources. To improve the protection of the Blue Amazon, in 2008, the Brazilian Navy (BN) started multi-year investments in long-term defense projects such as the Submarine Development Program (PROSUB). Brazil’s budgetary framework operates on an annual appropriation cycle, and this thesis assesses its impact on the BN’s capital investments. The research focuses on PROSUB’s execution from 2020 to 2023, compares Brazil’s and the United States’ budgetary systems, and evaluates an alternative budgetary system’s ability to increase defense investments’ effectiveness in Brazil. Findings suggest Brazil’s current budget system leads to work stoppages, timeline extensions, and price increases, hampering PROSUB’s progress and predictability. Although the BN has implemented strategies to increase efficiency and align actions to the budget, issues persist. The research suggests that incorporating a multi-year appropriations mechanism into Brazil’s annual budget system could provide a more efficient framework for long-term execution. This approach may balance annual oversight with the need for long-term fiscal planning, improving the BN’s means to develop and maintain capabilities necessary to protect the Blue Amazon.